S112. ELUCIDATING THE CHRONOLOGY OF FLUCTUATIONS IN BASIC SYMPTOMS, EARLY SIGNS AND PSYCHOTIC SYMPTOMS IN ESTABLISHED PSYCHOSIS USING REPEATED MEASURES DATA GATHERED USING A SMARTPHONE APP. (18th May 2020) - Eisner, Emily; Drake, Richard; Emsley, Richard; Barrowclough, Christine; Bucci, Sandra
Abstract: Background: Psychosis relapses are common, have profound adverse consequences for patients, and are costly to health services. 'Early signs' (e.g. anxiety; insomnia) have been used to predict relapse, in the hope of prevention or mitigation, with moderate sensitivity and specificity. Recent studies have provided preliminary prospective evidence that assessing 'basic symptoms' (e.g. vivid colour vision; disturbances in expressive speech) in addition to conventional early signs improves relapse prediction. Basic symptoms are assumed to be one of the earliest, most basic subjective expressions of the underlying neurobiological disruption preceding the development of psychosis. There is some empirical evidence from ultra-high risk groups suggesting that basic symptoms do indeed emerge prior to other risk indicators during the prodromal period. However, no studies to date have examined the relative timing of increases in basic symptoms, conventional early signs and psychotic symptoms in individuals with established psychosis. In the current study, we used time-lagged, repeated measures, prospective data to test whether increased basic symptoms would precede increased conventional early signs, and in turn increased psychotic symptoms. Methods: Individuals who had experienced a relapse of psychosis within the past year (n=18) were asked to use a smartphone app ('ExPRESS') weekly for six months to report early signs, basic symptoms and psychotic symptoms. Participants completed 65% of app assessments over the 6 month follow-up period, providing >200 observations in total. These data were analyzed using mixed effects models to account for clustering within individuals and to allow for missing data. Results: App items showed high concurrent validity with researcher-rated psychotic symptoms (ρ range 0.80 to 0.87, p<0.001) and basic symptoms (ICC=0.76, p<0.001) over six months. The results of the mixed effects analyses described above will be presented in full, and their theoretical and clinical implications will be discussed. Discussion: We anticipate that the findings of this study will be of theoretical interest. Within the socio-developmental-cognitive model (Howes & Murray, 2014), it would be logical to equate basic symptoms with the initial 'anomalous experiences' that are proposed to occur as a result of a disrupted dopamine system. Conventional early signs may then either occur later in the deterioration process laid out in the model or, as a heterogeneous group, may relate to more than one stage of the process. The results of the current study may help to elucidate the place of basic symptoms and conventional early signs within the socio-developmental-cognitive model. The findings may also lend support to the idea that basic symptoms are dopaminergic in origin.